Mutual accountability in African agricultural transformation - Ulimwengu, John M.; Matchaya, Greenwell C.; Makombe, T.; Oehmke, J. (International Food Policy Research Institute, 2020)
This chapter aims to deepen our understanding of both the conceptual framework of mutual accountability and its best practices in the context of agricultural transformation in Africa. We do so in three ways: documenting the need for and growth of mutual accountability mechanisms over time, discussing how mutual accountability processes contribute to agricultural transformation, and examining the effectiveness of the mutual accountability processes of choice— JSRs and the African agricultural BR. In the next section, we provide a brief review of the origins and theory of mutual accountability as well as its application in African agriculture. Following that, we discuss how mutual accountability is being operationalized through JSRs and the Malabo BR, and the effectiveness of the two processes. The section after empirically assesses the contribution of mutual accountability to agricultural transformation in Africa. The final section provides concluding remarks for driving agricultural transformation through mutual accountability processes.